PERHATIAN FILSAFAT TERHADAP SCIENCE (OBSERVASI, HIPOTESIS, INDUKSI, FALSIFIKASI, TEORI DAN EKSPLANSI) - syafriwana, syafriwana (STAI YAPIS Takalar, 2023)
This research delineates the role and purpose of philosophy in the pursuit of truth through profound thinking, while considering distinctions with empirical sciences. Philosophy, as an abstract discipline, investigates everything that exists or may exist logically. A comparison is drawn between observation in science and theoretical interpretation that can influence the understanding of phenomena. The discussion encompasses the concept of induction by Aristotle and the falsification approach by Karl Popper in the context of testing scientific theories. Theory, as scientific knowledge, has two realities, namely abstract and concrete, and yields rational explanations for why certain phenomena occur. The text also examines the differences between fundamental and derivative theories in science. Scientific explanation is defined as a statement that answers questions about how and why an event occurs, with an emphasis on the distinction between universal and object-specific theories. Overall, the text explores key concepts in philosophy and science, highlighting scientific and explanatory approaches to understanding reality.